2018
DOI: 10.1111/ijac.13048
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and electrical conductivity of La0.9Sr0.1 Ga0.8Mg0.2O2.85‐Ce0.8Gd0.2O1.9 composite electrolytes for SOFCs

Abstract: (100‐x) wt.% La0.9Sr0.1 Ga0.8Mg0.2O2.85 ‐ x wt.% Ce0.8Gd0.2O1.9 (x = 0, 5, 10, 20) electrolytes were prepared by solid‐state reaction. The composition, microstructure, and electrical conductivity of the samples were investigated. At 300 ~ 600°C, the pure La0.9Sr0.1 Ga0.8Mg0.2O2.85 electrolyte has a higher conductivity compared to the composite electrolytes, but at 650 ~ 800°C the 95 wt.% La0.9Sr0.1 Ga0.8Mg0.2O2.85 ‐ 5 wt.% Ce0.8Gd0.2O1.9 composite electrolyte presents the highest conductivity, reaching 0.035 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…The open circuit voltage (OCV) and current density only reached ~0.5 V and 0.32 A cm −2 , respectively. The maximum power output was ~0.16 W cm −2 at 800 °C , which is lower than the published data [23,31,32] for Ce0.9Gd0.1O1.95-1mol% MgO (0.47 W cm −2 at 700 °C ) [40], La0.9Sr0.1Ga0.8Mg0.2O2..85-Ce0.8Gd0.2O1.9 (60 W cm −2 at 700 °C ) [22], Ce0.8Sm0.15Ca0.05O1.875 (0.170 W cm −2 at 700 °C ) [34], and La0.85Sr0.15Ga0.8Mg0.2O2.825 (0.185 W cm −2 at 700 °C ) [41]. The fuel cell performance is relatively poor, which will limit the use of CSYG-BIT07 in SOFCs.…”
Section: Single Cell Performancecontrasting
confidence: 56%
“…The open circuit voltage (OCV) and current density only reached ~0.5 V and 0.32 A cm −2 , respectively. The maximum power output was ~0.16 W cm −2 at 800 °C , which is lower than the published data [23,31,32] for Ce0.9Gd0.1O1.95-1mol% MgO (0.47 W cm −2 at 700 °C ) [40], La0.9Sr0.1Ga0.8Mg0.2O2..85-Ce0.8Gd0.2O1.9 (60 W cm −2 at 700 °C ) [22], Ce0.8Sm0.15Ca0.05O1.875 (0.170 W cm −2 at 700 °C ) [34], and La0.85Sr0.15Ga0.8Mg0.2O2.825 (0.185 W cm −2 at 700 °C ) [41]. The fuel cell performance is relatively poor, which will limit the use of CSYG-BIT07 in SOFCs.…”
Section: Single Cell Performancecontrasting
confidence: 56%
“…Besides, an excessive sintering and poor densification yield in an excessive grain growth and the presence of pores, which are trapped among the grains or grain boundaries, blocking oxygen ion migration. Both contributions lead to a decrease in the conductivity of LSGM [37][38][39].…”
Section: Electrical Properties and Conductivity Measurementsmentioning
confidence: 99%
“…Therefore, the strontium and magnesium-codoped lanthanum gallate-based electrolyte (LSGM) emerges as a promising intermediate-temperature electrolyte material . It is reported that the optimal composition of strontium and magnesium doping is concluded as the formula of La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3‑δ , which reveals excellent pure oxygen ion conductivity at intermediate temperature, good chemical stability, and high mechanical strength. As there are few studies on LSGM electrolyte-based DC-SOFCs which directly use raw brown coal as fuel, it is meaningful to explore the feasibility of highly efficient utilization of real-world coal fuel for LSGM electrolyte-based cells. , …”
Section: Introductionmentioning
confidence: 99%